Expression and transformation of loyalty in a contractual service setting: A processual view. Issue 2 (May 2019) - Quach, Sara; Hewege, Chandana; Le, Viet
Highlights: There is a need to focus on loyalty sustainability, i.e. post-loyalty development. There are six possible transformative states of loyalty in a service context. Different transformative states involve different levels of emotional energy. Loyalty can be expressed in emotional, self-concept, and ritual aspects. Abstract: The main objectives of this study are twofold: (1) to gauge the expressions of loyalty toward a service provider, (2) to identify possible transformations of loyalty in the contractual service settings. Using an integrative theoretical perspective, the study presents a more holistic understanding of the dynamics of loyalty transformation taking a processual view. Following an interpretive research approach, we conducted twenty-eight semi-structured interviews with customers and managers of major mobile telephony service providers. The findings confirm that customer loyalty can transform into various states: (1) fanaticism, (2) stage of transition, (3) point of disinterest, and (4) state of betrayal. Moreover, it is determined that customers could express their loyalty to the service provider in several ways signifying their concern, advocacy, rituals, identification, beliefs, and nostalgic feelings. Chinese Abstract: 本研究的主要目的有两方面: (1) 衡量消费者对服务提供者的忠诚度表达, (2) 确定在契约服务环境中消费者忠诚度可能发生的转变.本研究采用整合的理论视角, 从过程的角度对忠诚度转化的动力机制进行了整体的理解.通过解释性研究方法, 我们对主要移动电话服务提供商的客户和经理进行了28次半结构式访谈.研究结果证实, 顾客忠诚度可以转化为不同的状态: (1) 狂热阶段, (2) 过渡阶段, (3) 无兴趣阶段, (4) 背叛阶段.此外, 顾客可以通过多种方式表达对服务提供者的忠诚度, 以显示他们的关心, 支持, 仪式, 认同, 信念和怀旧情绪.